Critical Analysis of Application of Article 303 BIS Paragraph (1) to 1 of The Criminal Code in Accessible Cases Online Gambling (Universitas Negeri Semarang, 2022)
Gambling in Indonesia is distinguished into two, ordinary gambling regulated in the Criminal Code and online gambling as stipulated in Law No. 11 of 2008 on Information and Electronic Transactions. Defendant Aan alias Andi committed a crime of online gambling by the way the defendant became an online gambling agent and the defendant was tasked with sharing the access code namely password and ID to the players who wanted to become members of the defendant’s online gambling. The defendant will benefit from the players using the defendant’s access code. The problem that the researchers reviewed relates to the application of Article 303 bis paragraph (1) to 1 of the Criminal Code by the judge on criminal acts making accessible gambling content carried out by defendant Aan alias Andi. Writing these laws using methods approach juridical normative that focused on research on data library. The specification of research that used a descriptive analytical, namely give a description data and carefully as completely as possible about the object of the problem as the result of the study library various literature, legislation, and other ingredients that deals with discussion at in writing the study case. Based on the results of the research, it is known that: First, the judge decided that the defendant Aan namely Andi used Article 303 bis paragraph (1) to 1 of the Criminal Code which was inappropriate because in Article 303 bis paragraph (1) to 1 of the Criminal Code there was no element of making gambling content accessible and making gambling content accessible has been specifically regulated in Article 27 paragraph (2) of the ITE Law. Second, Decision Number 184/Pid.B/2018/PN.Btm does not reflect the objectives of the law, namely justice, certainty and expediency which will have an impact on the weakness of the law enforcement process for the crime of gambling due to the low sentence given by the panel of judges.